2016
DOI: 10.18632/oncotarget.13760
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and propranolol combination prevents cancer progression and metastasis in different breast cancer models

Abstract: Discovery of new drugs for cancer treatment is an expensive and time-consuming process and the percentage of drugs reaching the clinic remains quite low.Drug repositioning refers to the identification and development of new uses for existing drugs and represents an alternative drug development strategy.In this work, we evaluated the antitumor effect of metronomic treatment with a combination of two repositioned drugs, metformin and propranolol, in triple negative breast cancer models.By in vitro studies with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 59 publications
4
51
1
1
Order By: Relevance
“…Metformin therapy weakens the risk of glioma-initiating cells (48), and inhibits ovarian cancer by increasing sensitivity to cisplatin (49,50), endometrial cancer through changes in Ki-67 proliferation (51-53), and breast cancer (54,55) and non-small cell lung carcinomas (56,57). Laboratory studies on breast cancer have shown that metformin increases the mean life span by 8% and mammary adenocarcinoma latency by 13.2% (P<0.05) in HER2/neu mice (58).…”
Section: Discussionmentioning
confidence: 99%
“…Metformin therapy weakens the risk of glioma-initiating cells (48), and inhibits ovarian cancer by increasing sensitivity to cisplatin (49,50), endometrial cancer through changes in Ki-67 proliferation (51-53), and breast cancer (54,55) and non-small cell lung carcinomas (56,57). Laboratory studies on breast cancer have shown that metformin increases the mean life span by 8% and mammary adenocarcinoma latency by 13.2% (P<0.05) in HER2/neu mice (58).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth was analyzed by measuring tumor length (a) and width (b) with a caliper, and by calculating tumor volume (V) with Eq. 2 [51]:…”
Section: Repositioning Of Anti-parasitic Drugsmentioning
confidence: 99%
“…Among breast cancer subtypes, triple-negative breast cancer exhibits distinct characteristics, is particularly aggressive and frequently recurrent, and becomes metastatic [3]. These subtypes of tumors account for 15% of all breast cancer types with higher percentages in premenopausal African-American and Hispanic women, and it is associated with very poor prognosis and limited treatment option availability [51]. As shown in Fig.…”
Section: Effect Of Abz and Rbz And Their Cyclodextrin Inclusion Complmentioning
confidence: 99%
“…Recent studies have shown that β-AR antagonists reduce breast cancer metastasis in vivo [17,104]. Additionally, a combination therapy of propranolol with metformin, a drug used in diabetes mellitus type 2, decreased migration, invasion, and proliferation of five breast cancer cell lines in vitro [125]. A clinical study conducted recently demonstrated that propranolol reduces Ki-67 and Bcl-2 markers in a stage III breast cancer patient.…”
Section: The Bone Marrow Microenvironment As a Target To Treat Breastmentioning
confidence: 99%